Sustainable Projects Run for the Low Mixteca Region in the State of Puebla, Mexico - Morales Olán, Gema; Moreno Zarate, Pedro; Rodríguez Bautista, Cristal de Rosa; Limón Galindo, María de Lourdes; Pachón Marín, Angelica (Ingeniería Solidaria, 2017)
Introduction: The results of three projects carried out at the Instituto Tecnológico Superior de Tepexi during 2014-2015 are presented, which were aimed at the development of one of the poorest regions in Mexico. Method: The first project consisted in the preparation of an oral hygiene product from the shoquillo plant (Rhus chondroloma), for which infusions of the plant with other species were evaluated, determining their acceptance through a sensory analysis. In the second project, a building block was made of marble cutting waste, which was combined with other construction products, and their physicochemical properties were determined based on the standards applicable to these products. The last project consisted in the manufacture of a strap from pet bottles, checking its resistance and elongation. Results: It is possible to develop a natural oral hygiene product that is pleasant to the senses when combining the plant extract with mint and peppermint. Using marble powder, a non-structural block was obtained, thus making use of this waste and avoiding pollution. The strap made from pet meets the requirements to be used by industries in the region. Conclusion: The projects have enabled the institute’s academic community to interact with the communities where they were carried out, since the main objective is to make an impact on the sustainable development of the region.